Keragaman Konsumsi Keluarga TKI dan Keluarga Non TKI Desa Curahnongko Kecamatan Tempurejo Kabupaten Jember - Naufilatul Qomariyah; Sunlip Wibisono; Rafael Purtomo (e-Journal Ekonomi Bisnis dan Akuntansi, 2019)
This study aims to find out how the diversity of family consumption of migrant workers and non migrant workers, and how much influence the remittance to the consumption of family of migrant workers covering consumption of capital expenditure, food consumption, non-food consumption and total consumption. And how much influence the income on the consumption of non-migrant family which includes consumption of capital expenditure, food consumption, non-food consumption, and total consumption. To achieve these objectives used primary data obtained directly from the place of study. The method of analysis used in this research is Simple Linear Regression Analysis. The results of this study indicate that remittance variable has a positive influence on consumption of capital expenditure, food consumption, non-food consumption, and total consumption of families of migrant workers. And remittance variables also have a significant influence on consumption of capital expenditure, food consumption, non-food consumption, and total consumption of families of migrant workers.. The income variable has a positive effect on consumption of capital expenditure, food consumption, non-food consumption, and total consumption of Non-migrant family workers. And income variables also have a significant effect on consumption of capital expenditure, food consumption, non-food consumption, and total consumption of Non-migrant family workers.Keywords: Consumption, Remittance, Revenue, Capital Expenditure Consumption, Food Consumption, Non-Food Consumption, Total Consumption.